Optimizing agronomic practices for pineapple (Ananas comosus (L). Merr. ‘MD-2’ cultivar) production based on growth stages - Vásquez Jiménez, J. (2023)
Introduction – Descriptions of the developmental stages of crops are necessary for optimal scientific communication and technology transfer between researchers, technicians, and farmers. Although pineapple cultivation is an intensive technical activity, there is no precise description of the crop’s phenology. The purpose of this study is to accurately describe visually identifiable vegetative (V) and reproductive (R) phenological stages (PS) during the development of the pineapple plant. Materials and methods – Plants of the cultivar ‘MD-2’ were planted in three different environments in Costa Rica. The same substrate and management practices were applied in the experimental plots. The V-stages were described based on the 5/13 phyllotaxy of the pineapple plant, while the R-stages were defined according to standard names commonly found in the literature but more precisely and systematically. Results and discussion – Five vegetative and six reproductive (PS) were proposed and developed using the cultivar ‘MD-2’. These stages can be used to describe the life cycle of ‘Smooth Cayenne’ and other cultivars that are its offspring, such as ‘CO2’ and ‘MD-2’ , that are of great economic importance worldwide. Conclusion – The discrete and visual identification of the (V) and (R) life cycle stages of the pineapple plant will provide a more precise basis on which to schedule cultural practices that require precision. This identification of stages will improve scientific communication and technology transfer between researchers, technicians, and growers. It will also provide a basis for proposing improvements for pineapple production and the development of computational models for growth prediction.